Calorific value of the sewage sludge in the thermal dryer - Zakaria, M.S. (Asian Research Publishing Network, 2015)
Recently, the increasing population as well as tremendous of industrial development has caused the production of sewage sludge rise sharply and the available solution for their disposal cannot afford the amount of sludge produced. In Malaysia, the main solution for sewage sludge disposal is by landfill. However, most of the landfill reaches its capacity and the production of sewage sludge continuously increasing. The available land space for disposal of sewage sludge is limited due to high demand for population for housing and urban. Therefore, there is a needed for a new disposal method for treating sewage sludge that can sustain and environmentally friendly. Converting this waste into energy can resolve the disposal problem of sewage sludge and generate the new sources of energy to human kind. However, the moisture content is sewage sludge is high which more than 85 of moisture content. In order to convert into energy, the small scale disc dryer was developed in order to reduce the moisture content of the sewage sludge which into acceptable level is less than 20 of moisture content for conversion into solid fuel. In this paper, the basic characteristic of the dried sewage sludge for conversion into energy was studied. Besides that, the effect of the temperature of the thermal dryer on the calorific value of the sewage sludge also being investigated. The higher temperature of the thermal dryer will reduce the calorific value of the sewage sludge. The maximum calorific value of the sewage sludge was obtained from the lowest power rating of the burner which is 135 kW which is 12.51 MJ/kg whereas the lowest calorific value of the sewage sludge was obtained from the highest power rating of the burner which is 315 kW which is 4.57 MJ/kg. Â© 2006-2015 Asian Research Publishing Network (ARPN).